Legal Analysis of Qurban Meat Distribution to Non-Muslim Citizens from a Maslahah Perspective - Gumri Panawari Lubis; Hasan Matsum; Dhiauddin Tanjung (Universitas KH. Abdul Chalim Mojokerto, 2025)
This article aims to explain the legal analysis of the distribution of sacrificial meat to non-Muslims from a maslahah perspective. In this article there are two problems that the author will resolve, namely: first, what is the opinion of the ulama regarding the law of distributing sacrificial meat to non-Muslims. Second, how to analyze the law of distributing sacrificial meat to non-Muslims from a Maslahah perspective. This research uses a qualitative method, which is carried out by collecting, analyzing and comprehensively interpreting narratives on visual data to obtain complete, thorough and holistic insight into the legal analysis of the distribution of sacrificial meat to non-Muslims from a maslahah perspective. The results of this research show that: first, the law on the distribution of sacrificial meat to non-Muslims among the ulama has very different opinions, if seen from the opinion of the majority of ulama, they say that it is permissible (makruh) to give food from sacrificial meat to non-Muslims in general. Furthermore, a minority of ulama are of the opinion that it is not permissible to give anything from sacrificial meat to non-Muslims at all.